2015
DOI: 10.1140/epjc/s10052-015-3507-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dynamics of scalar bosons in a cosmic string background

Abstract: The quantum dynamics of scalar bosons embedded in the background of a cosmic string is considered. In this work, scalar bosons are described by the Duffin-KemmerPetiau (DKP) formalism. In particular, the effects of this topological defect in the equation of motion, energy spectrum, and DKP spinor are analyzed and discussed in detail. The exact solutions for the DKP oscillator in this background are presented in closed form.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 61 publications
4
74
2
Order By: Relevance
“…We note that the result obtained in Eq. (35) is similar to the one reported in [2] for scalar bosons described by the Duffin-Kemmer-Petiau (DKP) formalism. …”
Section: Klein-gordon Oscillator In the Cosmic String Spacetimesupporting
confidence: 84%
See 1 more Smart Citation
“…We note that the result obtained in Eq. (35) is similar to the one reported in [2] for scalar bosons described by the Duffin-Kemmer-Petiau (DKP) formalism. …”
Section: Klein-gordon Oscillator In the Cosmic String Spacetimesupporting
confidence: 84%
“…Moreover, to make a consistent quantum field theory in a gravitational background, it is necessary to analyze the single particle states, in this way, efforts have been made in order to find an adequate formulation of the relativistic equation of motion for particles in a curved spacetime. In recent years, there has been a significant increase of interest in the study of gravitational effects on quantum mechanical systems (single particle states) [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. In this context it has been shown that the energy spectrum associated with one-electron atoms in an arbitrary curved spacetime is different from the one obtained in the usual flat Minkowski spacetime [4].…”
Section: Introductionmentioning
confidence: 99%
“…to Ω → 0 have also addressed, and the energy eigenvalues (24) is obtained which is found different from the result obtained in [30] for α → 1 there.…”
Section: Discussioncontrasting
confidence: 62%
“…These are constrained by the cosmic microwave background [6][7][8][9][10] and gravitational wave facilities [11][12][13][14][15]. In recent developments, cosmic strings have been considered to study solutions of black holes [16], to investigate the average rate of change of energy for a static atom immersed in a thermal bath a e-mail: hadisobhani8637@gmail.com of electromagnetic radiation [17], to study Hawking radiation of massless and massive charged particles [18], to study the non-Abelian Higgs model coupled with gravity [19], in the quantum dynamics of scalar bosons [20], in hydrodynamics [21], to study the non-relativistic motion of a quantum particle subjected to magnetic field [22], to investigate dynamical solutions in the context of super-critical tensions [23], describing scattering states of the Dirac equation in the presence of cosmic string for Coulomb interaction [24] and to study the spin-zero Duffin-Kemmer-Petiau equation in a cosmic-string space-time with the Cornell interaction [25].…”
Section: Introductionmentioning
confidence: 99%